2015
DOI: 10.2147/ndt.s86103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maintenance lithium treatment on serum parathyroid hormone and calcium levels: a retrospective longitudinal naturalistic study

Abstract: ObjectiveThe aim of this retrospective longitudinal naturalistic study was to evaluate the effects of maintenance lithium treatment on parathyroid hormone (PTH) and calcium levels.MethodsA retrospective longitudinal naturalistic study design was used. Data were collected from the database of a tertiary psychiatric center covering the years 2010–2014. Included were bipolar patients who had never been exposed to lithium and had lithium started, and who had PTH, and total and ionized calcium levels available befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
9
0
3
Order By: Relevance
“…Lastly, according to our regression model, higher levels of PTH are predicted by a pharmacological treatment with lithium. This result is in line with available studies, which have found that a long-term treatment with lithium stimulates the parathyroid function, leading to a secondary hyperparathyroidism [ 51 ]. Although the real prevalence of this phenomenon is unclear, about 25% of lithium-treated patients have disturbances in the calcium homeostasis [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Lastly, according to our regression model, higher levels of PTH are predicted by a pharmacological treatment with lithium. This result is in line with available studies, which have found that a long-term treatment with lithium stimulates the parathyroid function, leading to a secondary hyperparathyroidism [ 51 ]. Although the real prevalence of this phenomenon is unclear, about 25% of lithium-treated patients have disturbances in the calcium homeostasis [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis of relevant studies found that lithium treatment was associated with a 10% increase in blood calcium and PTH levels (McKnight et al 2012). Studies published since then have mostly confirmed this finding (Albert et al 2013, 2015; Shine et al 2015). There is some evidence that lithium-associated hypercalcemia/hyperparathyroidism is associated with fewer clinical symptoms than are seen in primary hyperparathyroidism (Shapiro and Davis 2015).…”
Section: Lithium and The Kidneysmentioning
confidence: 75%
“…Sonraki yıllarda yapılan çalışmalarda lityum ile ilişkili hiperparatiroidiye (LİH) bağlı hiperkalseminin görülme sıklığı %3,6-62 gibi geniş bir aralıkta bulunmuştur (Albert ve ark. 2013, Albert ve ark. 2015, Awad ve ark.…”
Section: Introductionunclassified
“…Karaciğer, böbrek yetmezliği ve vitamin D yetersizliği sekonder hiperparatirodiye; sekonder hiperparatiroidi çok uzun süre devam ederse tersiyer hiperparatiroidiye neden olabilir. En sık tersiyer hiperparatiroidi nedenleri kronik böbrek hastalığı, uzun süreli yüksek fosfat düzeyi ve düşük 1,25-dihidroksi vitamin D düzeyi olmasına rağmen (Fraser 2009) vitamin D düzeyi sadece üç çalışmada değerlendirilmiştir (Albert ve ark. 2015, Meehan ve ark.…”
Section: Introductionunclassified
See 1 more Smart Citation